DETERMINING ISOSBESTIC POINT AND DETERMINATION OF P-NITROFENOL COMPOUND by SPEKTROFOTOMETRI - Heru Pratomo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2003)
The determined of isosbestic point from weak acids or weak bases areusually important for indicator solutions. The indicators that used in acid-base titration have pH exactly, and this is usefulfor determine the end of titration. The aims of this research are (1) to determine ofwavelength on isosbestic point of p-nitro phenol, and (2) to determine of dissociation constant of p-nitro phenol. The determined of isosbestic has done with spectrophotometric method, to the p-nitro phenol solutions in several pH, at region of wavelength between 280 nm - 450 nm. In this research, indicate that the isosbestic point ofp-nitro phenol at the wavelength of 348 nm, and pH about 6.7. From this research also can be determined that the dissociation constant (KaYof p-nitro phenol is 6.48 x 10-8,not too different compared with K, literature, is7.08 x 10-8.